EFEKTIVITAS PENERAPAN PROGRAM DALUNG SMART VILLAGE SEBAGAI WUJUD PELAYANAN PUBLIK DI DESA DALUNG - Made Kembar Sri Budhi; Putu Dian Putri Chantika Pramiswari (E-Jurnal Ekonomi Pembangunan, 2025)
The implementation of the Dalung Smart Village program shows a phenomenon of uneven program socialization, the community's need for improved infrastructure and facilities, and the quality of human resources that support the program still needs improvement in order to realize the village government's vision and excellent public service quality. The purpose of this study is to analyze, explore, and obtain empirical evidence regarding the relationship between village apparatus performance, community accessibility, and community participation in the effectiveness of the Dalung Smart Village program. The population in this study is the Dalung Village community, including heads of households, spread across 23 hamlets with a sample size of 100 heads of households as respondents. The sampling technique used in this study is Cluster Random Sampling. The type of data in this study are quantitative and qualitative. Empirical data were collected through observation, questionnaires, and interviews. The data analysis technique used is multiple regression analysis. The average effectiveness level of each research variable shows a sufficiently effective result. The results of the analysis indicate that the performance of village apparatus and community accessibility have a positive and significant impact on the effectiveness of the Dalung Smart Village program. Meanwhile, community participation shows results that are contrary to the variables of village apparatus performance and community accessibility, specifically, it does not have a positive and significant impact on the effectiveness of the Dalung Smart Village program.